Physical growth and nutritional status of Mexican infants from newborn to two years of age Crecimiento físico y estado de nutrición de los niños mexicanos, del nacimiento a los dos años de edad - Samuel Flores-Huerta; Miguel Klünder-Klünder; Onofre Muñoz-Hernández (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To determine the nutritional status of Mexican infants under two years of age. MATERIALS AND METHODS: Five nutritional surveys, three being representative of the nation, were assessed using several anthropometric indicators, with reference to the WHO 2006 growth standard. RESULTS: From national surveys, the incidence of low birth weight ranged from 8.9 to 8.1% and was higher in rural areas. At two years of age, the prevalences of stunted growth, wasting and being overweight ranged from 25.6 to 16.1%, 4.5 to 1.9% and 6.3 to 10.8%, respectively, between 1988 and 2006. The combination of being overweight with stunted growth increased with age, particularly in rural areas. Figures presented in non-national surveys compared with national surveys demonstrate a lower incidence of low birth weight, similar levels of stunted growth, being overweight and obesity, and a little higher for wasting. CONCLUSION: Policies are required to be implemented to prevent nutritional diseases associated with stunted growth, being overweight and obesity. OBJETIVO: Conocer el estado nutricio de niños mexicanos menores de dos años. MATERIAL Y MÉTODOS: De cinco encuestas, tres de ellas nacionales, se evaluaron varios indicadores antropométricos, usando como referente el estándar de crecimiento de OMS, 2006. RESULTADOS: En las encuestas nacionales la incidencia de peso bajo al nacer va de 8.9 a 8.1%, siendo mayor en las áreas rurales. A los dos años de edad la prevalencia de desmedro va de 25.6 a 16.1%; de emaciación de 4.5 a 1.9% y la de sobrepeso y obesidad va de 6.3 a 10.8%, en 1988 y 2006 respectivamente. El sobrepeso concurrente con desmedro aumenta conforme aumenta la edad, especialmente en áreas rurales. Las cifras en las encuestas no nacionales, comparadas con las nacionales, muestran menor incidencia de peso bajo al nacer, valores similares para desmedro y sobrepeso y ligeramente mayores para emaciación. CONCLUSIÓN: Se requieren políticas de salud para prevenir enfermedades de rezago como desmedro y otras emergentes como el sobrepeso.